PENDIDIKAN BERWAWASAN MORAL MENGHASILKAN SDM ANTI KORUPSI - Arif Arif (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Multi-dimension crises including moral crisis (corruption) indicate the failure ofeducation. The lack of transparency and accountability in the field of politics andeconomy worsens the condition. Various research results show that corruption abolition should instigate from self-commitment at individual level. Each individul anticorruption commitment becomes the underpinning for collective commitment. Education in this case may become the medium for the collective commitment conscientization since commitment as a main characteristic of mature human being can be nurtured through education. Education thus makes humans to be more fully human. The state of being “fully human” itself represents the anticipated objective of education. What needs to be noted is that education may become the development instrument for each individual and community if utterly facilitated with good morality of educators. Education might not breed corrupt human beings if the educators themselves are not corrup